2016
DOI: 10.1007/s40135-016-0102-3
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Approaches to Glaucoma Management of Boston Keratoprosthesis Type 1

Abstract: Glaucoma remains a prevalent disorder and visual limiting factor after Boston keratoprosthesis type 1 implantation. Patients with glaucoma have worse initial and late visual acuity outcomes after otherwise successful keratoprosthesis implantation. Management of glaucoma in the setting of a keratoprosthesis is challenging because of relatively rapid progression and an inability to accurately measure intraocular pressure (IOP). In addition, there are no standard guidelines for glaucoma surveillance and monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Tube erosion can also be minimized with placement in the vitreous cavity versus the anterior chamber, and the tube can be reinforced with a patch graft made of fascia lata, pericardium, sclera, cornea, or dura mater. 4,14,15 The removal and replacement of the contact lens will vary. In general, the contact lens should be worn continuously and removed for cleaning and disinfection in office at each follow-up visit.…”
Section: Discussionmentioning
confidence: 99%
“…Tube erosion can also be minimized with placement in the vitreous cavity versus the anterior chamber, and the tube can be reinforced with a patch graft made of fascia lata, pericardium, sclera, cornea, or dura mater. 4,14,15 The removal and replacement of the contact lens will vary. In general, the contact lens should be worn continuously and removed for cleaning and disinfection in office at each follow-up visit.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, there is limited space for a glaucoma tube in the anterior chamber after keratoprosthesis implantation; the average functional anterior chamber depth is 0.21 mm. 18, 19 Secondly, angle closure in eyes with keratoprosthesis is prevalent, extensive and progressive. 19 Anterior segment OCT has demonstrated that anterior chamber depth and anterior chamber angle dimension are dynamic in these eyes and previous reports have documented anterior chamber tube occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma drainage device (GDD) placement and endoscopic or transscleral diode cyclophotocoagulation are highly effective modalities used for IOP control in most publications. 19,[65][66][67] Most studies advocate prior GDD surgery or concurrent BKPro and GDD implantation in eyes with preexisting glaucoma. 67,68 Lentis and colleagues demonstrated that eyes receiving BKPro plus GDD implantation had significantly lower IOP than eyes receiving BKPro alone with no significant difference in the rate of serious vision-threatening complications.…”
Section: Glaucoma-associated Complicationsmentioning
confidence: 99%
“…19,[65][66][67] Most studies advocate prior GDD surgery or concurrent BKPro and GDD implantation in eyes with preexisting glaucoma. 67,68 Lentis and colleagues demonstrated that eyes receiving BKPro plus GDD implantation had significantly lower IOP than eyes receiving BKPro alone with no significant difference in the rate of serious vision-threatening complications. 69 Combined pars plana vitrectomy and GDD implantation is a suitable alternative that has shown good efficacy in IOP control with a decreased risk of complications 70,71 (Figure 3).…”
Section: Glaucoma-associated Complicationsmentioning
confidence: 99%
See 1 more Smart Citation